A Knowledge-Based Stress Diagnosis System Using the Certainty Factor Approach and DASS-42 Psychological Indicators - Winangsari Pradani; Syarifah Hani; Siti Rahmawati; Ade Jamal; Andi Arniaty Arsyad (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2025)
Stress is a natural physiological and psychological response to everyday demands, yet chronic stress can impair cognitive functioning, emotional regulation, sleep quality, social interaction, and academic or occupational performance. Access to mental health professionals remains limited and early detection is crucial. To address this issue, this study developed a Depression, Anxiety, and Stress Scale-42 (DASS-42)–based expert system for stress diagnosis using the Certainty Factor (CF) method. A key contribution of this work is the active involvement of licensed psychologists in knowledge elicitation, rule construction, symptom weighting, and iterative validation, ensuring clinical accuracy, reliability, and interpretability. The system underwent functional, usability, and diagnostic testing. Black Box Testing confirmed full feature performance (100%), indicating strong system stability. Usability evaluation using the System Usability Scale (SUS) produced a score of 78.375 (Grade B+, “Good”), with the highest acceptance among students and employees, and lower ratings from users with limited digital literacy. Diagnostic validation using 20 test cases assessed by two certified psychologists yielded an average accuracy of 87.5%, showing strong agreement between system results and expert judgment. These findings demonstrate that CF-based reasoning effectively models clinical evaluation of 13 stress indicators from DASS-42, indicating the system’s feasibility a reliable early stress-screening tool.Keywords— Certainty Factor, DASS-42, Expert System, Mental Health Screening, Stress Diagnosis